2013
DOI: 10.1021/nn401274e
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of CuInTe2 and CuInTe2–xSex Ternary Gradient Quantum Dots and Their Application to Solar Cells

Abstract: We report the first synthesis of colloidal CuInTe2, CuInTe2-xSex gradient alloyed quantum dots (QDs) through a simple hot injection method. We confirmed the composition of synthesized QDs to cationic rich phase of CuIn1.5Te2.5 and Cu0.23In0.36Te0.19Se0.22 with XPS and ICP analysis, and we have also found that the gradient alloyed Cu0.23In0.36Te0.19Se0.22 QDs exhibit greatly improved stability over the CuIn1.5Te2.5 QDs. The solution-processed solar cell based on the gradient alloyed Cu0.23In0.36Te0.19Se0.22 QDs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
72
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 56 publications
4
72
1
Order By: Relevance
“…One potentially attractive, yet not well-studied, copper-based material is CuFeSe 2 , which represents a well-known class of I-III-VI 2 group ternary chalcogenides. Among the I-III-VI 2 group, such as CuInS 2 [22,23,24], CuInSe 2 [24,25,26], CuInTe 2 [27] and CuFeS 2 [24,28,29,30], materials have attracted extensive attention due to their high absorption coefficient, high conversion efficiency, low toxicity and other physical properties and unique chemical properties and have been explored for the fabrication of photovoltaic solar cells in very recent years. However, among these, less attention been paid to the CuFeSe 2 material, as eskebornite with a narrow band gap of 0.16 eV belongs to the tetragonal structure type [31] and the crystal structure of the CuFeSe 2 has the space group Ptrue42c with cell parameters a = 5.521 Å and c = 11.04 Å [32].…”
Section: Introductionmentioning
confidence: 99%
“…One potentially attractive, yet not well-studied, copper-based material is CuFeSe 2 , which represents a well-known class of I-III-VI 2 group ternary chalcogenides. Among the I-III-VI 2 group, such as CuInS 2 [22,23,24], CuInSe 2 [24,25,26], CuInTe 2 [27] and CuFeS 2 [24,28,29,30], materials have attracted extensive attention due to their high absorption coefficient, high conversion efficiency, low toxicity and other physical properties and unique chemical properties and have been explored for the fabrication of photovoltaic solar cells in very recent years. However, among these, less attention been paid to the CuFeSe 2 material, as eskebornite with a narrow band gap of 0.16 eV belongs to the tetragonal structure type [31] and the crystal structure of the CuFeSe 2 has the space group Ptrue42c with cell parameters a = 5.521 Å and c = 11.04 Å [32].…”
Section: Introductionmentioning
confidence: 99%
“…133 Besides the above mentioned type I, type II, and inverted type I core/shell QDs, there is a kind of gradient alloyed QDs in which the element transition is not abrupt in the QDs. 134 Kim et al 133 reported a simple hot injection method to synthesize the colloidal CuInTe 2−x Se x gradient alloyed QDs with the highest selenium content at the surface of the applications to solar cells. …”
Section: Surface Passivationmentioning
confidence: 99%
“…Synthesis and function optimization of nanostructured I‐III‐VI2 chalcopyrite materials including CuInTe 2 have been extensively studied. Researchers have prepared different types of CuInTe 2 nanostructures including nanoplates, quantum dots and nanocubes . However, preparation of well‐aligned CuInTe 2 nanowires has not been reported to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%